Characteristics of People Returned to Prison From Medium Secure Psychiatric Services in England and Wales: National Cohort Study - Leonard, Sarah; Webb, Roger T.; Doyle, Michael; Shaw, Jennifer (Frontiers in Psychiatry, 2022)
Background We recently published the first study to establish the circumstances by which MSS ‘prison-transfer’ patients are returned to prison. Of particular concern was the finding that a quarter of prison-transfer patients were returned to prison by Responsible Medical Officers (RMOs) because they were not engaging with treatment or were deemed too ‘high risk’ to remain detained within the services, circumstances that would be unacceptable when considering discharge via a community care pathway. It is important to further explore the characteristics of people admitted to MSSs from prison, and to investigate how these may differ for individuals who are returned to prison, as compared to those discharged into the community. Aim To describe the characteristics of prison-transfers who receive an RMO directed discharge from MSSs, and; to compare these characteristics by discharge destination; prison return and community discharge. Methods Prospective cohort comparative study: all prison-transfer patients discharged under the instruction of their RMO over a six-month period, from 33 NHS medium secure units across England and Wales. Data on patient demographic, clinical and legal characteristics were extracted via full patient health record review and collateral information from clinicians was also obtained. This information was used to complete The Historical, Clinical and Risk – 20 items (HCR-20v3) and The Structured Assessment of Protective Factors (SAPROF). Individuals who were returned to prison were compared with those who were discharged to the community. Results Persons returned to prison represented a vulnerable group at time of discharge as compared to those discharged into the community and had a significantly shorter length of stay in MSSs. Over half of those returned to prison had a length of stay of less than six months. Individuals returned to prison displayed significantly more issues with psychological adjustment at time of discharge, and had a higher risk of future violence and a lower prevalence of protective factors that mitigate subsequent risks of relapse and reoffending. Discussion MSs in England and Wales are returning vulnerable individuals to prison in lieu of adequate aftercare services. The role of and responsibilities of MSSs as regards admissions from prison needs to be reconsidered.